Collaborative Governance: Strategies for Addressing Challenges and Opportunities in MSME Development - Afrijal Afrijal; Nadia Nadia; Raihan Rahma Hanina; Helmi Helmi; Nurul Kamaly (Indonesian Journal of Public Administration Review, 2025)
This study focuses on Collaborative Governance in Addressing the Challenges and Opportunities of MSME Development. The development of MSMEs in Indonesia often faces various obstacles, including limited business networks and opportunities, a constrained business environment, difficulties in accessing global markets, inadequate human resource capacity, insufficient business coaching, low digital literacy, and other structural barriers. These challenges require serious attention from the government to enhance the role of MSMEs as a key driver in realizing community-based economic independence. The purpose of this study is to examine and analyze government strategies for MSME development through multi-stakeholder engagement. The research employs a literature study method using both primary and secondary data obtained from journals, books, documentation, and other relevant scholarly sources aligned with the research topic. The findings suggest that a collaborative governance approach provides innovative and solution-oriented perspectives for accelerating the development of MSMEs. This is because the involvement of multiple stakeholders—such as government, private sector, communities, and other related actors—can foster a cross-sectoral collaborative ecosystem that is inclusive and sustainable. The success of MSMEs should not only be assessed through the existence of regulations and governmental involvement, but also through active cross-sector participation aimed at building trust and commitment to MSME empowerment and development. Collaboration thus becomes the key to delivering comprehensive, adaptive, and needs-based solutions for business actors. This multi-sectoral synergy represents a concrete step toward governance reform that is more open and responsive to MSME development, ultimately leading to the creation of globally competitive MSMEs.